Хлопоты: повести и рассказы / Александр Рекемчук ; [предисловие Д. Тевекеляна] - Рекемчук Александр Евсеевич (Советская Россия, 1976)
Экземпляры: Аб (1976) / Инвентарный номер: 54987 / Авт.знак: Р 36 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6